ANALYSIS OF CHARACTER EDUCATION CONTENT IN PRIMARY SCHOOL SCIENCE TEXTBOOKS IN THE INDEPENDENT CURRICULUM - Widyatika, Dinda; Riandika, Lucky Nindi (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2023)
The development of character-based interactive learning media in science learning in elementary schools aims to increase students' understanding of science material while integrating character values. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. At the analysis stage, the need for learning media that is relevant to the curriculum and student needs is identified. The design stage produces an interactive media design that combines science material with character values ​​such as discipline, responsibility and cooperation. The development stage involves creating media using interactive software that is easily accessible to students. At the implementation stage, the media is tested in class to determine its effectiveness, while at the evaluation stage an assessment of student learning outcomes and character development is carried out. The research results show that the use of character-based interactive learning media can increase students' understanding of science concepts and strengthen the character values ​​instilled during learning. This media also received a positive response from students and teachers, who found the media interesting, easy to use, and effective in learning. Thus, the development of this learning media can be an innovative alternative in supporting the achievement of educational goals in elementary schools.